Charismatic leadership in local politics: A study of the political articulation of power in Kalipare, Malang Regency - Khoiron Khoiron; Rico Tomboti (Publisia: Jurnal Ilmu Administrasi Publik, 2025)
This article examines the practice of political articulation of power carried out by a Village Head during their leadership. The practice of articulating power is ethical but also political because the public understands that what is done is a sign of power politics that can be said to be "unique" and anti-mainstream. In the current political tradition, community improvement actions are often carried out because of disappointment or dissatisfaction with someone's leadership. On the contrary, in Malang, there was mass action, but they forced the incumbent to be willing to advance again in the political contestation in the second period of the election. This study aims to reveal the meaning of the practice of power articulation that becomes a political practice. This study uses a qualitative method with a purposive sampling technique on four informants whom the researchers chose based on data validity. Therefore, several research results were found using qualitative research analysis, data collection, data reduction, data presentation, and conclusions, including 1) blusukan and absorbing aspirations, 2) light-hearted leaders, and 3) leaders of the people. From here, the markers of charismatic leadership were articulated by Gaguk during his tenure as the village head of Kaliarsi Villa.